2011
DOI: 10.1029/2011gl047498
|View full text |Cite
|
Sign up to set email alerts
|

Stress drop variations of induced earthquakes at the Basel geothermal site

Abstract: [1] We determine stress drops from P-wave spectra of about 1000 earthquakes induced by hydraulic stimulation in crystalline rock for a deep heat mining project in Basel, Switzerland. We observe an increase in stress drop by about a factor of five with radial distance from 10 m to 300 m, which suggests that stress drop correlates with pore pressure perturbations due to the injection. We test this hypothesis by calculating the injection-related pore pressure perturbation based on a simple linear pore pressure di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
147
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(166 citation statements)
references
References 29 publications
18
147
1
Order By: Relevance
“…Isotropic moment tensor components may relate to the occurrence of long-period events (Bame and Fehler, 1986;Ferrazzini et al, 1990;Jousset et al, 2010). The locations of the events with high isotropic components also coincide with previously found regions of high -values (Bachmann et al, 2012) and low stress drops (Goertz-Allmann et al, 2011).…”
Section: Basel Switzerlandsupporting
confidence: 65%
See 2 more Smart Citations
“…Isotropic moment tensor components may relate to the occurrence of long-period events (Bame and Fehler, 1986;Ferrazzini et al, 1990;Jousset et al, 2010). The locations of the events with high isotropic components also coincide with previously found regions of high -values (Bachmann et al, 2012) and low stress drops (Goertz-Allmann et al, 2011).…”
Section: Basel Switzerlandsupporting
confidence: 65%
“…However, the multiple injection operations at TR8A can be responsible for changing dominant fluid migration pathways, and indirectly may be responsible for the occurrence of LME in the Berlin geothermal field. They also found a dependence of stress drop on distance from the injection point, somewhat similar to what was found by Goertz-Allmann et al (2011) for Basel, but not nearly as well defined.…”
Section: Source Mechanism Of Larger Magnitude Events (Lme)supporting
confidence: 64%
See 1 more Smart Citation
“…Goertz- Allmann et al (2011) analyzed stress drops of earthquakes induced by a waterinjection experiment into a borehole and obtained a clear increase in the stress drop as a function of distance from the injection point, thus suggesting that the stress drop correlates with pore pressure perturbations due to the injection. Tomic et al (2009) estimated stress drops of reservoir-induced earthquakes with M ≤ 2.1 and concluded that the values were similar to those of natural earthquakes.…”
Section: Studies On Seismicity and Stress Dropmentioning
confidence: 99%
“…[78,79]. In the case of forced fluid circulation in a geothermal field, it is also possible that a reduction of differential stress due to pore pressure increase leads to reduced stress drop, as observed by Goertz-Allmann et al [80]. Finally, the self-similarity of earthquakes characteristics, such as stress drop versus seismic moment, is still subject of debate, although several observations for both earthquakes and induced seismic events are consistent with constant stress drops for magnitudes ranging between 9 and -4, e.g.…”
Section: Intact Rock (Red Line) Which In Addition Have Cohesion (C)mentioning
confidence: 59%